The impact of bagworm (Metisa plana) attack on the production of oil palm (Elaeis guineensis Jacq.) at Tanjung Beringin Plantation PT. Langkat Nusantara Kepong - Arie Hapsani Hasan Basri; Stephanie Angelica Girsang; Aisar Novita (International Journal of Biosciences and Biotechnology, 2022)
The impact of bagworm (Metisa plana) attack on the production of oil palm (Elaeis guineensis Jacq.) at Tanjung Beringin Plantation PT. Langkat Nusantara Kepong. This study aims to assess the extent of attack by bagworms (Metisa plana) and the impact of bagworm attacks (Metisa plana) on oil palm production in Tanjung Beringin Plantation PT. Langkat Nusantara Kepong. The study method used was descriptive statistics by collecting data from the estate office and direct interviews. The study was carried out at Afdeling III Tanjung Beringin Plantation, PT. Langkat Nusantara Kepong. The assessment was carried out from February to July 2022. The statistical analysis method used to determine the impact of bagworm (Metisa plana) attacks on oil palm production was using tables, graphs and Descriptive Statistics analysis. The results of tables, graphs and Descriptive Statistics analysis show that the attack area of the bagworm (Metisa plana) in 2019-2021 has decreased by 66.62% and the attack of the bagworm (Metisa plana) has an impact on oil palm production. The wider the pest attack, the smaller the production. Pest attacks in 2019 of 680 Ha experienced a decline in production in 2020 by 2.33% and pest attacks in 2020 of 374 Ha experienced an increase in production in 2021 by 11.60%.